Chronic administration of nano-sized PAMAM dendrimers in vivo inhibits EGFR-ERK1/2-ROCK signaling pathway and attenuates diabetes-induced vascular remodeling and dysfunction - Akhtar, Saghir; Chandrasekhar, Bindu; Yousif, Mariam H. M.; Renno, Waleed; Benter, Ibrahim F.; El-Hashim, Ahmed Z. (Elsevier Science Bv, 2019)
We investigated whether chronic administration of nano-sized polyamidoamine (PAMAM) dendrimers can have beneficial effects on diabetes-induced vascular dysfunction by inhibiting the epidermal growth factor receptor (EGFR)-ERK1/2-Rho kinase (ROCK)-a pathway known to be critical in the development of diabetic vascular complications. Daily administration of naked PAMAMs for up to 4 weeks to streptozotocin-induced diabetic male Wistar rats inhibited EGFR-ERK1/2-ROCK signaling and improved diabetes-induced vascular remodeling and dysfunction in a dose, generation (G6 > G5) and surface chemistry-dependent manner (cationic > anionic > neutral). PAMAMs, AG1478 (a selective EGFR inhibitor), or anti-EGFR siRNA also inhibited vascular EGFR-ERK1/2-ROCK signaling in vitro. These data showed that naked PAMAM dendrimers have the propensity to modulate key (e.g. EGFR) cell signaling cascades with associated pharmacological consequences in vivo that are dependent on their physicochemical properties. Thus, PAMAMs, alone or in combination with vasculoprotective agents, may have a beneficial role in the potential treatment of diabetes-induced vascular complications. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Polyamidoamine; EGFR; Cell signaling; Diabetes; Vascular complications